The Christchurch mosque shooting, the media, and subsequent gun control reform in New Zealand: a descriptive analysis. Issue 2 (4th March 2021) - Every-Palmer, S.; Cunningham, R.; Jenkins, M.; Bell, E.
Abstract : In March 2019, a mass shooting at two Christchurch mosques, livestreamed to Facebook, resulted in the deaths of 51 people. Psychologically, this served as a focusing event with high threat salience, shocking a country unused to gun violence despite its comparatively lax firearm legislation. The unprecedented reluctance by the New Zealand media to feature the shooter as a protagonist or even publish his name, concentrating instead on victims and societal issues, helped promote a sense of collective responsibility for change. This was strongly modeled by political leaders. Within weeks, new gun control laws were introduced with bipartisan support. We present this as a national case study, considering psychological and societal enablers for legislative reform in response to extreme gun violence. The shooting also raised the intractable problem of the internet allowing terrorists to promulgate violent content and extremist ideology with regulation in this area harder to achieve than gun control.